Dynamic Complexity of Positive and Negative Affect in NSSI – A Daily Diary Study - Michaela Bruckbauer-Schwed; Tim Kaiser; Marc Keglevic; Anton-Rupert Laireiter (Clinical Psychology in Europe)
[Background] Non-suicidal self-injury (NSSI) is a major health problem. Functionally, it is related to affect instability and increased affective intensity. The role of negative emotions has already been extensively explored, only few studies have focused on positive emotions. The concept of dynamic complexity (DC) is particularly well suited to differentially analyze the dynamics of affect collected by ecological momentary assessment (EMA). This study examines DC of positive and negative emotions in individuals with and without NSSI history in an EMA setting. [Method] Participants from a clinical NSSI group (n = 28) and a comparable clinical non-NSSI control group (n = 33) completed the Positive and Negative Affect Schedule (PANAS) once a day between six to 37 days (M = 15.60, SD = 5.80). DC was calculated for the assessed time-series of daily affect. Additionally, we fitted a linear mixed model to predict positive and negative dynamic complexity with length of stay and group. [Results] Compared to controls, individuals with a history of NSSI showed significantly more positive affect and had significantly higher DC in affect in general. No significant difference for negative affect was found. [Conclusion] Our results suggest that it is important to assess dynamic emotional patterns and to analyze in detail the role of positive and negative affect in individuals with NSSI in order to better understand the complex interplay between the different emotional states and to be able to use it for diagnostic purposes and clinical interventions.